The Improvement of Mathematical Creative Thinking Abilities Based on Self-Confidence Category in Senior High School Students - Hayati Ramadhani Putri; Kusnandi Kusnandi; Al Jupri; Hayati Ramadhani Putri; Kusnandi Kusnandi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The development of mathematical creative thinking abilities has become an essential focus in 21st-century education, yet students’ performance in this area remains relatively low, particularly when influenced by affective factors such as self-confidence. This study aims to examine the effectiveness of the Treffinger learning model, assisted by GeoGebra, in improving students’ mathematical creative thinking abilities, and to analyze differences in improvement across self-confidence categories (high, medium, and low). The research employed a quantitative quasi-experimental design with a pretest–posttest non-equivalent control group design. The study was conducted with senior high school students, where the experimental class received Treffinger learning assisted by GeoGebra, while the control class received conventional instruction. Data were collected through tests of mathematical creative thinking ability and a self-confidence questionnaire and analyzed using normalized gain and inferential statistical tests. The results revealed that the improvement in students’ mathematical creative thinking abilities in the experimental class was significantly greater than in the control class across all self-confidence categories. These findings indicate that the Treffinger model, assisted by GeoGebra, is effective in enhancing both the cognitive and affective aspects of learning. Therefore, integrating innovative learning models and technology is recommended to foster students’ creative thinking and support their self-confidence in learning mathematics.